A comparative study of art therapy in cancer patients receiving chemotherapy and improvement in quality of life by watercolor painting. (February 2017) - Bozcuk, H.; Ozcan, K.; Erdogan, C.; Mutlu, H.; Demir, M.; Coskun, S.
Highlights: We show in a sample of 72 cancer patients that watercolor painting (PATP) as a form of art therapy improves quality of life and depression. Moreover, PATP is feasible in patients during their chemotherapy sessions. We advise art therapy in general and PATP in particular for cancer patients while on active treatment. Abstract: Background: There is limited data on the role of art therapy used in cancer patients. We wanted to test the effect of painting art therapy provided by a dedicated professional painting artist on quality of life and anxiety and depression levels in patients having chemotherapy. Methods: Cancer patients having chemotherapy in the day unit of a medical oncology department of a university hospital were offered to take part in a painting art therapy program (PATP). This program consisted of a professional painting artist facilitating and helping patients to perform painting during their chemotherapy sessions while they were in the day unit, as well as supplying them painting material for home practice. The changes in quality of life domains of EORTC-QLQ-C30 questionnaire and in Hospital Anxiety and Depression Scores (HADS) were assessed before and after the PATP. These results were contrasted with a reference group of cancer patients on chemotherapy but not taking part in the PATP. In order to adjust for multiple comparisons of quality of life parameters between patient groups, we utilized the Bonferroni correction. Results: A total of 48 patients, of which 26 patients did and 22 did not have prior exposure to PATP, were enrolled in the PATP. A control group of 24 patients who did not have any PATP activity during the study period also took part in the study. With PATP, there was significant improvement in global quality of life (F = 7.87, P = 0.001), and depression scores (F = 7.80, P = 0.001). Conclusions: To our knowledge, this is the largest comparative PATP experience in cancer patients on chemotherapy and show that PATP is feasible in the clinics. Our results confirm that art therapy in the form of painting improves quality of life and depression in cancer patients having chemotherapy. This effect was more pronounced in patients without any previous experience of PATP.